Pengembangan layanan sarana baca virtual menggunakan aplikasi flip book di perpustakaan perguruan tinggi - Dwi Fajar Saputra (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2017)
University library services in the digital era is identical with the information technology-based innovation. Flip book application can be presented to become part of the innovation. The Library of Medicine Faculty, UPN Veteran Jakarta trying to develop virtual read tools service application using the flip book. The method used is from Pressman’s called the waterfall model. The waterfall model is planning, design, programming and testing. After the development is finish, obtained that the flip book application can be developed with the additional source code from the side of the web server. The added source code is the javascript, one of programming language and the framework is turn.js. The test was conducted by the local in the Windows 7 operating system and for online version at the Centos 6 operating system. The test results that the flip book application can be running well and can be used as an alternative service innovation in university library.